“A dverii u nei 30...”: The Doorways of the Faceted Palace in Novgorod the Great - Antipov, Ilya V.; Yakovlev, Dmitriy E.; Trushnikova, Alexandra V. (Actual Problems of Theory and History of Art, 2021)
The chronicles describe the Faceted Palace commissioned by the archbishop Evfimiy II in 1433 with ample details: it took the builders from “Beyond the Sea” 95 days to erect the edifice with 30 doorways. The restoration of the Faceted Palace in 2006–2012 gave opportunity to study the surviving 27 doorways. Their structure and decoration varies between rather simple and more intricate and falls into two categories. None of them have lintels, but all are spanned with segmental arches. The first type has either straight jambs or jambs with protrusions. These portals lead to the facilities, intramural staircases, heating chambers, and latrines. The majority of the doorways belong to the second type that has jambs with protrusions and extra vertical recesses to secure the door. In some cases, the second type is complicated by several jambs and lancet archivolt above the tympanum. Such portals are located in the galleries (“Seni”) and mark the important and representative halls. In general, the portals are important accents in the rhythm of the facades, and their decoration correlates with the hierarchy of the interiors.The chronicler paid attention to the numerous doorways to highlight the unusual for the Novgorod architecture dimension and structural complexity of the Faceted Palace. The gothic decoration of the church portals has long been implemented into the local tradition, but they differ from the 1433 Palace. The comparison with the 14th–15th century brick gothic architecture provides numerous analogies in various parts of the Baltic region, and therefore sheds no light on the origin of the German master-builders. In conclusion, it is worth to mention the hierarchy of the portals as another trait inherited by the Faceted Palace builders from the main residence of the Grand Master of the Teutonic Order in Marienburg.This publication has been completed with the support of the Russian Science Foundation (RSF), project № 18-18-00045 “Civil stone architecture of Novgorod (14th–15th centuries): a complex study”.
Keywords: Old Russian architecture; Novgorod the Great; stone civil buildings; door openings; architecture of brick Gothic